Odra i jej znaczenie dla regionu .......... 11 (Samorząd terytorialny na Dolnym Śląsku: Sprawy, dylematy i wyzwania, 2025)
THE ODER RIVER AND ITS SIGNIFICANCE FOR THE REGIONThe paper provides a thematic and chronological (and at times retrospective) overview of the Oder River as reflected in Polish discourse across various historical periods and subject areas, representing diverse expectations and perspectives. This major waterway located in the heart of Central Europe has long fascinated numerous nations and geopolitical actors in the region. The author reviews and systematises selected themes related to the river—not only as a hydrological, climatic, and economic phenomenon, but also as a key factor in major geopolitical events, particularly in the twentieth century. An additional focus of the study is the presence of the Oder River in public discourse concerning the city of Wrocław.